The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5021/ad.2010.22.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Marketed Cosmetic Products Constituents with the Antigens Included in Cosmetic-related Patch Test

Abstract: Background: Currently, cosmetic series (Chemotechnique Diagnostics, Sweden) is the most widely used cosmeticrelated patch test in Korea. However, no studies have been conducted on how accurately it reflects the constituents of the cosmetics in Korea. Objective: We surveyed the constituents of various cosmetics and compare with the cosmetic series, to investigate whether it is accurate in determining allergic contact dermatitis caused by cosmetics sold in Korea. Methods: Cosmetics were classified into 11 catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A study in Seoul found that not all antigens that are found in cosmetics are actually available in patch test kits and that these could be potential allergens which go undetected; hence, a need for regular modification of testing kits to reflect ingredients in the cosmetics is advocated [ 15 ]. In India, a study on pediatric contact dermatitis revealed that children could be sensitive to some of the cosmetic antigens and the sensitization may happen due to early age of cosmetic use [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Seoul found that not all antigens that are found in cosmetics are actually available in patch test kits and that these could be potential allergens which go undetected; hence, a need for regular modification of testing kits to reflect ingredients in the cosmetics is advocated [ 15 ]. In India, a study on pediatric contact dermatitis revealed that children could be sensitive to some of the cosmetic antigens and the sensitization may happen due to early age of cosmetic use [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common causes of ACD are minerals such as nickel, chromium, cobalt, gold and organic chemicals [3]. In Korea, lacquer [4], rubber [5], hair dye [6], minerals (such as nickel, chromium, cobalt, and mercury), and cosmetics [7] are the main causes of ACD. Those chemicals work as haptens, which induce an immune response only when attached to larger molecules.…”
Section: Introductionmentioning
confidence: 99%